Nursing interventions in cases of agitation and dementia. (May 2014) - Oppikofer, Sandra; Geschwindner, Heike
This study had two objectives: firstly, to assess and compare the frequency and circumstances of agitation and, secondly, to generate decision-making aids for the treatment of agitation patients by applying a nursing intervention in cases of dementia and agitation. For that purpose, 1002 measurements of open nursing interventions in cases of agitation were obtained over a period of 11 weeks in two nursing homes in the city of Zurich and in the nursing home Sonnweid. Before, during and after two intervention periods of four weeks each, data were collected for 60 persons suffering from severe dementia. The results show that two-thirds of the residents were never agitated, one-quarter was moderately agitated and only very few suffered from medium-to-severe agitation. In almost half the cases, agitation occurred while the person was alone (46%), followed by cases of agitation as a constant state (26%). There was rarely any agitation while the residents were engaged in activities. After analysing 433 documented cases, it turned out that the most successful care interventions were avoiding noise, accompanying the person to the toilet, communication/validation, walking about/movement and administering beverages. Being based on newly translated observational methods and a unique longitudinal study design with combined intervention, this study provides important insights into how agitation in dementia can be influenced within the care context, as well as a practical evaluation of interventions specific to different institutions.